(untitled) (Journal of Small Business Strategy (archive only), 1998)
Small businesses can reap a variety of benefits by classifying some of their workers as "contract workers" rather than "employees." However, there are significant risks involved as well. This article explains the issues and regulations involved in such a classification, gives some examples, and then provides the small business owner, manager and advisor with a series of guidelines to increase the likelihood of correct classification, maximum benefit and minimum risk to the company.